CHARACTERISTICS AND KINEMATICS OF RAM SPERMATOZOA MOVEMENT IN FERTILIZATION MEDIUM USING SERICIN - Arindya Andrian; Ni Wayan Kurniani Karja; Mohamad Agus Setiadi; Ekayanti Mulyawati Kaiin (BRIN - Badan Riset dan Inovasi Nasional, 2026)
This study aimed to evaluate the effectiveness of sericin on quality and kinematics of spermatozoa movement in fertilization medium and substituted for BSA in PEIV. Spermatozoa preparation was done with and without swim-up. Each group was incubated in fertilization medium with BSA, sericin 0.05%, 0.1%, 0.5%, and evaluated after addition of fertilization medium,15, 30, 60 minute. The results showed that the progressive motility values, sericin 0,5% group were higher than other groups (P<0.05). Membrane integrity showed differences between treatments. The VCL value showed no difference except for 0 and 30 minute swim-up group, sericin 0.5% was higher (P<0.05). VAP, VSL, LIN, and STR had no difference. The ALH at 30 minute swim-up and 60 minute without swim-up, sericin 0.5% were higher than others (P<0.05). In conclusion, the addition of sericin 0,5% has potential to replace BSA, sericin 0.5% can maintain quality and show early signs of hyperactivation of spermatozoa.